The effects of warm water immersion on blood pressure, heart rate and heart rate variability in people with chronic fatigue syndrome - Romy Parker; Zeenath Higgins; Zandiswa N.P. Mlombile; Michaela J. Mohr; Tarryn L. Wagner (AOSIS, 2018)
Background: Chronic fatigue syndrome (CFS) is a central sensitisation syndrome with abnormalities in autonomic regulation of blood pressure (BP), heart rate (HR) and heart rate variability (HRV). Prior to exploring the effects of hydrotherapy as a treatment for this population, changes in BP, HR and HRV during warm water immersion need to be established. Objectives: The study aimed to determine the effects of warm water immersion on BP, HR and HRV in adults with CFS compared to matched-pair healthy adults. Method: A quasi-experimental, single-blinded study design was used with nine CFS participants and nine matched controls. Participants' BP, HR and HRV were measured before, after 5 minutes and post warm water immersion at the depth of the fourth intercostal space, using the Ithlete® System and Dräger BP monitor. Results: There was a significant difference between groups in HRV prior to immersion (control group: 73 [55-74] vs. chronic fatigue syndrome group: 63 [50-70]; p = 0.04). There was no difference in HRV post-immersion. A significant difference in HR after immersion was recorded with the control group having a lower HR than those with CFS (78 [60-86] vs. 86 [65-112]; p = 0.03). The low HRV present in the CFS group prior to immersion suggests autonomic dysregulation. Individuals with CFS may have reduced vagal nerve activation post-immersion. During immersion, HRV of the CFS participants improved similar to that of the healthy controls. Conclusion: Prior to immersion, differences were present in the HRV of the participants with CFS compared to healthy controls. These differences were no longer present post-immersion. Clinical implications: Warm water immersion appears safe and may be beneficial in the management of individuals with CFS.